1874 Cal. Stat. 465, An Act For the Protection of the Property At East Park, in Sacramento County, ch. CCCXXI (311), § 1 - (:unkn) unknown (General Publisher, 1874)
Prohibited discharge of any gun, pistol, or firearm within the grounds of East park of Sacramento
--
Keywords: DISCHARGE